THE INCIDENCE OF CORONARY RISK FACTORS, ESPECIALLY THE DIAGONAL EAR LOBE CREASE IN THE DISTRICT OF ISFAHAN, IRAN - A.Nafissi; B.Teimouri (Tehran University of Medical Sciences, 1978)
Over a period of four years, we followed 200 male cases (Female patients were excluded from this study because from early childhood, the majority of Iranian girls have their ears pierced which tends to distort the ear lobe and renders the diagnosis of the crease difficult) of proved coronary artery disease (Angina Pectoris, coronary insufficiency, and myocardial infarction) in a private clinic in the district of Isfahan. Our attention was directed primarily to the prevalence of the so-called risk factors and especially to the newly recognized diagonal ear-lobe crease, described in various medical journals. Findings were 1) Our findings conformed approximately with the accepted classical coronary risk factors especially in the following: age range between 50-70 years in 71%; mesomorphic body build in 50%; personality type A in 60%, arterial diastolic pressure above 90m m of Hg in only 33%; cigarette smoking more than 10 per day in 43% and more than 20 per day in 15%; the other factors like obesity, diabetes (clinical and chemical), Hypercholesterolemia and sedentarism, were not significantly abnormal. 2) The diagonal ear lobe crease (see photograph) has been present in 65% of all CAD group. 3) The incidence of this crease increased with age from fifth decade on. 4) This crease was present in the single incidence of a fatal myocardial infarction which occurred in the case of a patient under 30 years of age. 5) In most cases there were multiple risk factors, among them the diagonal ear lobe crease, but in 12.5% of them, the crease was associated only with the personality type A (according to Friedmann typing). This may indicate some link between these two factors typing). This may indicate some link between these two factors requiring further research. In closing we should add that in 17% of a group of 21 apparently non-cardiac patients exhibiting this ear lobe crease the ECG showed signs of CAD. We may conclude that this rather simple sign of diagonal ear lobe crease may be counted as a risk factor in CAD, and by its simplicity might be used in the screening procedure for detecting coronary heart disease, in large sectors of the community, especially in the age group under 60 years.